2014
DOI: 10.1111/jpn.12161
|View full text |Cite
|
Sign up to set email alerts
|

Performance, serum amino acid concentrations and expression of selected genes in pair‐fed growing pigs exposed to high ambient temperatures

Abstract: Heat stress (HS) depresses pig performance mainly because of appetite reduction, although other factors involved in the cellular availability of nutrients may also contribute to that depression. An experiment was conducted with twelve pair-fed pigs (30.3 ± 2.7 kg BW) to examine the effect of severe HS (up to 45 °C) on the expression of genes coding for two cationic amino acid (AA) transporters (b(0,+) AT and CAT-1), leptin, heat-shock protein (Hsp-90) and myosin in several tissues; serum concentrations (SC) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 26 publications
4
21
0
5
Order By: Relevance
“…Also Nagayach et al (2017) observed an increase in HSP70 expression in liver and heart of goats during the summer. In agreement, we recently demonstrated that chronic HS increases the expression of HSP90 in liver, LD and duodenum of pigs (Morales et al, 2014;Cervantes et al, 2016). However, in the present study there was no effect of HS or feed intake on the expression of HSP70 in LD and ST muscles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also Nagayach et al (2017) observed an increase in HSP70 expression in liver and heart of goats during the summer. In agreement, we recently demonstrated that chronic HS increases the expression of HSP90 in liver, LD and duodenum of pigs (Morales et al, 2014;Cervantes et al, 2016). However, in the present study there was no effect of HS or feed intake on the expression of HSP70 in LD and ST muscles.…”
Section: Discussionsupporting
confidence: 91%
“…This response indicates that the increased HSP70 expression in muscle may occur during a short period of time, thus animals may start to acclimate to chronic HS conditions (Gaughan et al, 2013). Other studies with pigs (Morales et al, 2014), cattle (Bharati et al, 2017), goats (Dangi et al, 2015) and mice (Sareh et al, 2011) showed a reduction in HSP70 expression after chronic or repeated exposure to heat stress. This partially explains the lack of effect on expression of HSP70 in both muscles analyzed in the present experiment.…”
Section: Discussionmentioning
confidence: 90%
“…Morales et al (2016) also reported a greater loss of endogenous His recovered at the distal ileum of HS pigs. In addition, it was reported recently that HS markedly reduces the abundance of mRNA coding for the cationic AA transporter b 0,+ AT in the small intestine of pigs (Morales et al, 2014), which possess high specificity for Arg and His (Bröer, 2008). This may imply a reduced reabsorption of cationic endogenous Arg and His.…”
Section: Discussionmentioning
confidence: 92%
“…In summary, the digestibility of essential AA is differentially affected in pigs exposed to natural HS, and thus, special attention should be given to Arg and His when formulating diets for growing pigs under HS conditions. in the small intestine of HS pigs (Morales et al, 2014). Moreover, we recently reported an increased loss of endogenous AA in HS pigs (Morales et al, 2016).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation